2019
DOI: 10.1111/jch.13536
|View full text |Cite
|
Sign up to set email alerts
|

Association of thyroid function with white coat hypertension and sustained hypertension

Abstract: This study aimed to explore the relationship of thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4) levels with hypertension subtypes. 1056 euthyroid adults were included as research samples. They underwent measurement of clinic blood pressure and 24-hours ambulatory blood pressure monitoring. Then, they were divided into normotension (NT), white coat hypertension (WCH), masked hypertension (MHT), and sustained hypertension (SHT) groups. The 24-hours dynamic electrocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…Among the studies that reported 2 × 2 data (n = 66,767), 29 studies [ 9 , 11 , 20 34 , 40 , 58 – 63 , 66 , 72 – 74 ] used a CBPM cutoff threshold as ≥ 140/90 for diagnosis of HT, while one study [ 19 ] used the threshold of DBP > 95 mmHg and one study did not reported the threshold. The 24-h ABPM had a cut-off of ≥ 130/80 mmHg for 12 studies [ 11 , 26 , 31 33 , 58 , 59 , 61 – 63 , 74 ] and daytime ABPM had a cut-off of ≥ 135/85 mmHg for 16 studies [ 20 25 , 28 30 , 34 , 60 , 65 , 66 , 73 ]. Two [ 27 , 72 ] and one [ 19 ] studies applied daytime ABPM with cut-offs of ≥ 140/85 and DBP ≥ 95 mmHg, respectively (see Additional file 1 : Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies that reported 2 × 2 data (n = 66,767), 29 studies [ 9 , 11 , 20 34 , 40 , 58 – 63 , 66 , 72 – 74 ] used a CBPM cutoff threshold as ≥ 140/90 for diagnosis of HT, while one study [ 19 ] used the threshold of DBP > 95 mmHg and one study did not reported the threshold. The 24-h ABPM had a cut-off of ≥ 130/80 mmHg for 12 studies [ 11 , 26 , 31 33 , 58 , 59 , 61 – 63 , 74 ] and daytime ABPM had a cut-off of ≥ 135/85 mmHg for 16 studies [ 20 25 , 28 30 , 34 , 60 , 65 , 66 , 73 ]. Two [ 27 , 72 ] and one [ 19 ] studies applied daytime ABPM with cut-offs of ≥ 140/85 and DBP ≥ 95 mmHg, respectively (see Additional file 1 : Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…These pathological changes may cause the body's blood pressure to rise; however, many clinical studies have not found that subclinical hypothyroidism is related to office blood pressure [ 29 ]. In our previous studies, we have found that white-coat hypertension, masked hypertension, and sustained hypertension have their own thyroid function characteristics in the euthyroid participants [ 13 ]. For example, among patients with euthyroid, elevated TSH was only found in those with sustained hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The division method was based on the standards of our laboratory. The thyroid function standard of S-HYPO group was TSH greater than 5.60 uIU/ml; FT3, 3.09–7.42 pmol/l; FT4, 7.64–16.03 pmol/l, and the thyroid function in euthyroid group was TSH, 0.34–5.60 uIU/ml; FT3, 3.09–7.42 pmol/l; FT4, 7.64–16.03 pmol/l [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Faria Joao et al did not find an increased incidence of cardiovascular events in patients with nocturnal NT WCHT during a 7.6-year follow-up study [ 39 ]. However, abnormal glucose and lipid metabolism and cardiac structural changes in nocturnal normal WCHT have also been reported in many studies [ 12 , 40 ]. Whether WCHT also causes cardiovascular damage remains controversial.…”
Section: Discussionmentioning
confidence: 99%